GAYA KOMUNIKASI RELATIONSHIP GEN Z : PESAN, PESAN SUARA, DAN TELEPON - Nina Yuliana (Jurnal Komunikasi Dialogis, 2026)
Abstract - This qualitative study examines the communication styles adopted by Generation Z (Gen Z) in social and interpersonal interactions, focusing on the three most commonly used digital communication modes: text messaging, voice messaging, and phone calls (Siagian & Yuliana, 2024). As a generation growing up alongside continuous technological advancements, Gen Z exhibits communication behaviors shaped by digital convenience, efficiency, and adaptability (Prensky, 2001). Using a netnographic approach (Kozinets, 2015), this study analyzed 450 digital artifacts—including user comments, video transcripts, public text messages, and voice message content—from TikTok, Instagram, and X (formerly Twitter). Thematic analysis (Braun & Clarke, 2006) revealed four main themes: (1) text as the default mode for low-pressure asynchronous communication; (2) voice messaging as a hybrid medium for conveying emotional nuances; (3) phone calls as a last resort for urgent or formal situations; and (4) the emergence of a new digital etiquette, specifically the “text-before-call” norm (Christin, 2024). Findings indicate that Gen Z prioritizes flexibility, personal time control, and emotional comfort over the richness of synchronous communication. Text messaging dominates daily interactions due to its efficiency and unobtrusive nature, while voicemail serves as a middle ground when tone and emotion are important. Phone calls are increasingly avoided unless absolutely necessary, often causing anxiety when unexpected. This study concludes that Gen Z's communication style is characterized by pragmatism, contextual awareness, and a strong preference for boundary maintenance. These findings contribute to interpersonal communication theory by extending the Uses and Gratifications Theory (Katz, Blumler, & Gurevitch, 1973) to encompass affective needs and digital ethical norms. Practical implications for educators, employers, and digital platform designers are discussed.